Gerakan Masyarakat Sehat Dan Peduli Lingkungan Melalui Senam Pagi, Edukasi Sampah, Dan Penanaman Bibit Masyarakat RT. 10 Kelurahan Penurunan - Aziz Zurahman; Firdhan Satriawan Sakti; Alviyan Sahadi; Dimas Aldi Prandika; Lois Kapirosi; Yoli Andi Rozzi; Devi Sartika; Sri Narti (Utami Publisher, 2026)
This community service activity aims to increase physical health awareness and environmental concern for residents of RT 10 RW 04 Penurunan Village, Bengkulu City. The main problem faced is the lack of regular physical activity and the management of household waste that is not optimal. The methods used include direct action through morning exercises together, interactive education about waste sorting, and planting tree seeds as a greening effort. The results of the activity show an increase in citizen participation in fitness activities and a new understanding of the economic value of waste if managed properly. Through planting seeds, it is hoped that a more beautiful and healthy environment will be created in a sustainable way for the local community.